Income distribution and middle‐income groups across the world. Issue 1 (5th August 2013) - Richiardi, Pelin Sekerler; Corley‐Coulibaly, Marva; Kashef, Hassan
Abstract: Inequalities have widened over the past two years in most advanced economies ‐ thereby resuming the trend that preceded the onset of the global financial crisis; while the opposite trend is observed in emerging and developing countries. Similarly, the middle income group has been shrinking in the majority of advanced countries over the last decades while this group has significantly expanded in emerging and developing economies. However, a closer look at emerging and developing countries shows that progress remains fragile as poor and vulnerable people still represent the majority of the population.